Lung chronicles: decoding granulomatous disease; role of molecular study - Hasim, Husna Syaza; Zaki, Hafizatul Solehah; Mussadik, Umul Khairil Fatimah; Chng, Kay Ly (Academy of Medicine Malaysia., 2023)
Introduction: Granuloma alone is a nonspecific histopathological finding, rather it comprises a group of disorders which have a wide spectrum of pathologies. The integration of histological analysis and molecular study is crucial in concluding a case in the field of forensic pathology. Case report: A 43-year-old Malay gentleman was found unconscious at his home. Reportedly, he has no known medical illness but was an intravenous drug user and had multiple histories of prison detention, though he was not under custody at that moment. He had a short history of fever and shortness of breath. External examination revealed a cachexic, medium body-built with no marks of injury. However, upon opening the chest, there was generalized adhesion of the pleura with cavitations of bilateral lungs and copious amounts of pus-like secretions. Histological analysis of the lung sections showed presence of few multinucleated giant cells. Discussion: Presence of lung cavitations grossly, together with giant cells with or without granuloma histologically, were frequently associated with mycobacteria infection. This has not always been the case, particularly in the case reported above as the sample sent for molecular study did not detect mycobacteria. What is highlighted under the microscope will somehow need to be further investigated with molecular study, either to nullify or confirm the preliminary findings.